PENGARUH PENGETAHUAN KEUANGAN, SIKAP KEUANGAN DAN KEPRIBADIAN TERHADAP PERILAKU MANAJEMEN KEUANGAN PADA PELAKU UMKM DI KOTA SUNGAI PENUH - Dona Elvia Desi (Gapenas Publisher, 2022)
This study aims to see whether there is an influence and the magnitude of the influence between Financial Knowledge, Financial Attitude and Personality on Financial Management Behavior on MSME Actors in Sungai Full City in 2021. The sample used is 43 MSME actors in the city of Sungai Penuh and the analytical tools used multiple linear regression and determinant coefficients. The results were obtained that partially there is an influence between Financial Knowledge on financial management behavior in MSME actors in Sungai Penuh City in 2021. This is proven by the t value (3,042) greater than the t table value (2,022), partially there is no effect between financial attitudes towards financial management behavior among MSME actors in Sungai Penuh City in 2021. This is evidenced by the t-count value (- 0.26 ) which is greater than the t table value (- 2.022 ), partially there is no influence of Personality on Behavior Financial Management for MSME actors in Sungai Penuh City in 2021. This is proven by the t-count value (1.283) which is smaller than the t-table value (2.022), simultaneously Financial Knowledge, Financial Attitude and Personality affect Financial Management Behavior in MSME actors in Sungai Penuh City in 2021. This is proven by the larger F arithmetic F table ( 21,583 2.83 ). The magnitude of the influence of Financial Knowledge, Financial Attitudes and Personality on Financial Management Behavior on MSME actors in Sungai Full City in 2021 is 62.4%, which means Financial Management Behavior on MSME actors in Sungai Full City in 2021 is influenced by Financial Knowledge, Financial Attitude and Personality. While the remaining 37.6% is influenced by other variables not examined in this study